Recent advances in oral delivery of biologics: nanomedicine and physical modes of delivery. (3rd August 2018) - Vllasaliu, Driton; Thanou, Maya; Stolnik, Snjezana; Fowler, Robyn
ABSTRACT: Introduction : Research into oral delivery of biologics has a long and rich history but has not produced technologies used in the clinic. The area has evolved in terms of strategies to promote oral biologics delivery from early chemical absorption enhancers to nanomedicine to devices. Continued activity in this area is justifiable considering the remarkable proliferation of biologics. Areas covered : The article discusses some physiological barriers to oral delivery of biologics, with a special focus on less characterized barriers such as the basement membrane. Recent progress in oral delivery of biologics via nanomedicine is subsequently covered. Finally, the emerging field of device-mediated gastrointestinal delivery of biotherapeutics is discussed. Expert opinion : Oral delivery of biologics is considered a 'panacea' in drug delivery. Almost century-old approaches of utilizing chemical absorption enhancers have not produced clinically translated technologies. Nanomedicine for oral biologics delivery has demonstrated potential, but the field is relatively new, and technologies have not progressed to the clinic. Device-mediated oral biologics delivery (e.g. ultrasound or microneedles) is in its infancy. However, this space is likely to intensify owing to advances in electronics and materials, as well as the challenges and history related to clinical translation of alternative approaches.